Using Modified Intensive Early Stocking for Cow/Calf Production - Keith R. Harmoney; John R. Jaeger (Kansas Agricultural Experiment Station Research Reports, 2020)
Intensive early stocking (IES) was introduced nearly a half century ago in eastern Kansas and has since been adopted as a major management tool to increase animal production, efficiency of production, and economic return on tallgrass rangelands. These increases have come almost exclusively by using IES with young stocker animals. Intensive early stocking and its gains have been proven effective repeatedly in published research. A similar modified IES (MIES) system has increased production efficiency of stocker animals on western Kansas rangelands. Perennial grassland acres for cattle production, as well as cattle numbers, are declining. Using management practices that mimic the MIES system to increase beef cattle stocking density for breeding herds may allow producers to maintain or increase cow numbers for beef production on fewer perennial grassland resources. The objective of this project is to compare cow and calf growth and performance in traditional continuous season-long stocking (SLS) and MIES beef production systems.
Keywords: available herbage; body condition score; continuous season-long stocking; intensive early stocking; species composition